Combined Immunodeficiency in Patients With Trichohepatoenteric Syndrome - Vély, Frédéric; Barlogis, Vincent; Marinier, Evelyne; Coste, Marie-Edith; Dubern, Béatrice; Dugelay, Emmanuelle; Lemale, Julie; Martinez-Vinson, Christine; Peretti, Noël; Perry, Ariane; Bourgeois, Patrice; Badens, Catherine; et al. (Frontiers in Immunology, 2018)
The syndromic diarrhea/trichohepatoenteric syndrome (SD/THE) is a rare and severe bowel disorder caused by mutation in SKIV2L or in TTC37, 2 genes encoding subunits of the putative human SKI complex involved in RNA degradation. The main features are intractable diarrhea of infancy, hair abnormalities, facial dysmorphism, intrauterine growth restriction. Immunologically this syndrome is associated with an hypogammaglobulinemia and a rapid loss of specific antibodies after vaccination leading to an immunoglobulin supplementation. Immune evaluation of the French cohort of SD/THE patient revealed two main immunological defects. First, the count of switched memory B lymphocytes is very low and long-lasting production of specific antibodies is frequently impaired. Second, NK cell lymphopenia is associated with a reduced degranulation and IFN-γ production and these patients frequently present with EBV infection. Moreover, an immunological screening of patients with clinical features of SD/THE could facilitate the diagnosis.